Engineered anti-CRISPR proteins for optogenetic control of CRISPR–Cas9. (November 2018) - Bubeck, Felix; Hoffmann, Mareike; Harteveld, Zander; Aschenbrenner, Sabine; Bietz, Andreas; Waldhauer, Max; Börner, Kathleen; Fakhiri, Julia; Schmelas, Carolin; Dietz, Laura; Grimm, Dirk; Correia, Bruno; et al.
Abstract Anti-CRISPR proteins are powerful tools for CRISPR–Cas9 regulation; the ability to precisely modulate their activity could facilitate spatiotemporally confined genome perturbations and uncover fundamental aspects of CRISPR biology. We engineered optogenetic anti-CRISPR variants comprising hybrids of AcrIIA4, a potentStreptococcus pyogenes Cas9 inhibitor, and the LOV2 photosensor fromAvena sativa . Coexpression of these proteins with CRISPR–Cas9 effectors enabled light-mediated genome and epigenome editing, and revealed rapid Cas9 genome targeting in human cells. CASANOVA uses LOV and blue light to regulate CRISPR activity.